The Effect of Dynamic Geometry Software-Based Interactive Media with the RME Approach in Improving Critical Thinking on the Rotation Topic - Ramidha, Nur Fitriani; Shodikin, Ali; Abdullah, Abdul Halim (FKIP Universitas Lampung, 2025)
The Effect of Interactive Media Based on Dynamic Geometry Software with the RME Approach on Improving Critical Thinking in Rotation Material. Objectives: The goal of this research is to examine the effect of using interactive media on Dynamic Geometry Software (DGS), like GeoGebra, along with the Realistic Mathematics Education (RME) technique in improving students’ critical thinking on the topic of rotation in geometry. Methods: The study used both a quantitative approach and a quasi-experimental approach. There were 38 students from SMA Negeri 1 Olahraga Sidoarjo in East Java who took part in this study. The experimental class and the control class consist of 19 students each. The experimental group learned with GeoGebra-based interactive media and the RME method, while the control group learned more traditionally without technology and the RME method. A set of validated test questions was administered before and after the intervention to measure students’ critical thinking skills. Results: There was a significant difference between the two groups’ critical thinking skills. Students in the experimental class were much better at understanding, evaluating, and thinking about geometric rotation problems than students in the control class. Combining GeoGebra and RME helped students understand how rotation works in real life and made them more interested, active, and better at understanding, exploring, and using it in a meaningful way. Conclusion: The RME method and GeoGebra helped students think critically about geometry, especially rotation. These results support the idea that using technology in a way that makes learning mathematics more meaningful, like RME, can help students think more deeply. Teachers should think about using these kinds of strategies to help their students learn mathematics better. Keywords: critical thinking, geogebra, quasi-experimental, RME, rotation.